Electromagnetically Induced Transparency in Media with Rydberg Excitons 1: Slow Light - Ziemkiewicz, David (Entropy (Basel), 2020)
In this paper, we show that Electromagnetically Induced Transparency (EIT) can be realized in mediums with Rydberg excitons. With realistic, reliable parameters which show good agreement with optical and electro-optical experiments, as well as the proper choice of Rydberg exciton states in the Cu(2)O crystal, we indicate how the EIT can be performed. The calculations show that, due to a large group index, one can expect the slowing down of a light pulse by a factor of about [Formula: see text] in this medium.